Ultrathin nanofiltration membrane with polydopamine-covalent organic framework interlayer for enhanced permeability and structural stability - Wu, Mengyuan; Yuan, Jinqiu; Wu, Hong; Su, Yanlei; Yang, Hao; You, Xinda; Zhang, Runnan; He, Xueyi; Khan, Niaz Ali; Kasher, Roni; Jiang, Zhongyi (Journal of membrane science, 2019)
Nanofiltration is a promising technology towards desalination and water purification. However, the pursuit for separation efficiency was hampered by the thick and less controllable selective layer. Herein, the ultrathin composite membranes with enhanced nanofiltration (NF) performance were achieved by interfacial polymerization mediated by polydopamine (PDA)-covalent organic framework (COF) interlayer. The hybrid interlayer with exceptional surface hydrophilicity and high porosity controlled the adsorption/diffusion of amine monomers during the interfacial polymerization process and generated an ultrathin and dense polyamide (PA) layer, which was immensely reduced from 79 nm to 11 nm in thickness. The PA/PDA-COF/PAN nanofiltration membrane exhibited desirable desalination ratio (93.4% for Na2SO4) and dye rejection (94.5% for Orange GII), along with outstanding water permeation flux of 207.07 L m−2 h−1 MPa−1, 3 times higher than that of commercial NF membranes with similar solute rejection. Moreover, the hybrid interlayer significantly strengthened the interfacial interaction between the PA layer and the polyacrylonitrile (PAN) support, rendering the composite membrane with superior structural stability. The proposed strategy provided novel insight into the rational design of multifunctional interlayer to manipulate interfacial polymerization for high-performance PA membranes. [Display omitted] •The 11 nm-thick NF membranes were prepared on PDA-COF hybrid interlayer.•The hybrid interlayer controlled the adsorption/diffusion of amine monomers.•The PA/PDA-COF/PAN membrane showed highest water flux of 207.07 L m−2 h−1 MPa−1.•The TFC membranes exhibited high rejections to Na2SO4 (93.4%) and dyes (94.5–100%).•The PA/PDA-COF/PAN membrane showed satisfying structural stability.